2015
DOI: 10.12740/pt/28915
|View full text |Cite
|
Sign up to set email alerts
|

How can we help caregivers of patients with Alzheimer’s dementia?

Abstract: Social, family and professional life depending on diverse factors. The caregiver burden is mainly related to patients with behavioral disturbances (BPSD) and loss of cognitive functions. Caring for a patient with dementia directly links to significant psychological stress. it also affects the caregivers' physical and mental health. The psychiatric morbidity is higher among the caregivers population. Depression, anxiety disorder and insomnia have been found to be the most common. in this article, the authors sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The fifth major theme depicts family conflicts indicating that caregivers face hardships in relations, affected marital bond, disturbed home environment and financial crisis. This was supported by previous studies for example Rachel and Turkot (2015) reported economical and personal constraints, increased personal problems (Schulze & Rössler, 2005;Salama & El-Soud, 2012)and that close relations can further give birth to distress and conflicts as well (Stengard, 2002;Qualls & Zarit, 2009) and it even escalates if patient is living with his or her family.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The fifth major theme depicts family conflicts indicating that caregivers face hardships in relations, affected marital bond, disturbed home environment and financial crisis. This was supported by previous studies for example Rachel and Turkot (2015) reported economical and personal constraints, increased personal problems (Schulze & Rössler, 2005;Salama & El-Soud, 2012)and that close relations can further give birth to distress and conflicts as well (Stengard, 2002;Qualls & Zarit, 2009) and it even escalates if patient is living with his or her family.…”
Section: Discussionsupporting
confidence: 74%
“…Most often, caregivers with excessive burden are females, people with low social status, elderly individuals, and individuals with low educational levels. Certain factors that influence the feeling of burden are: tension, financial or personal constraints and even the relation before and during the disease between the caregiver and the patient (Rachel & Turkot, 2015).It is difficult to care for elderly Alzheimer patients. As a result of daily care needs, including changing, bathing feeding, day to day assistance and household work, care givers frequently fail to address their own needs sufficiently (Neumann & Dias, 2013).…”
mentioning
confidence: 99%
“…The results of a study by Rachel et al show that providing care for older people with low functional capability in their home environment generates caregiver's burden and negative changes in the quality of life (Rachel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%